2012
DOI: 10.1038/jhg.2012.34
|View full text |Cite
|
Sign up to set email alerts
|

Differences in allele frequencies of autosomal dominant hypercholesterolemia SNPs in the Malaysian population

Abstract: Hypercholesterolemia is caused by different interactions of lifestyle and genetic determinants. At the genetic level, it can be attributed to the interactions of multiple polymorphisms, or as in the example of familial hypercholesterolemia (FH), it can be the result of a single mutation. A large number of genetic markers, mostly single nucleotide polymorphisms (SNP) or mutations in three genes, implicated in autosomal dominant hypercholesterolemia (ADH), viz APOB (apolipoprotein B), LDLR (low density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This is because besides the SNPs being mono-allelic (non-polymorphic) [37], we also observed an almost equal number of the predicted risk alleles present in both case subjects and control subjects across our 252 samples. Thus analyses of these polymorphisms were not statistically significant and therefore, regarded as having non-pathogenic phenotype.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is because besides the SNPs being mono-allelic (non-polymorphic) [37], we also observed an almost equal number of the predicted risk alleles present in both case subjects and control subjects across our 252 samples. Thus analyses of these polymorphisms were not statistically significant and therefore, regarded as having non-pathogenic phenotype.…”
Section: Discussionmentioning
confidence: 58%
“…Han Chinese subjects, where available, were selected as the targeted group for comparison as this Asian ethnicity were believed to closely resemble the ethnic groups of our study population. The results demonstrated that six of our SNPs differed in the frequency of MAF in public database [37]. Disparity in frequency could be due to founder-effects, natural selection or multi-ethnic groups in the study population [7], [38] (Table 8).…”
Section: Discussionmentioning
confidence: 97%
“…Data from Singapore revealed a similar distribution of mutations as compared to other Asian countries (Pek et al, 2018). Data from Malaysia revealed significant differences in the allele frequency of markers for LDLR, APOB, and PCSK9 genes compared to publicly available data from other populations (Alex et al, 2012). Until now, there is limited literature discussing the genetic differences in FH between Asian and non-Asian populations.…”
Section: Genetic Differences Of Fh Between Different Ethnicitiesmentioning
confidence: 79%
“…Two independent studies from the same team in Malaysia used SNPs for genetic analysis (Alex et al, 2012;Lye et al, 2013). Although they found SNPs with different allele frequencies between Malaysians, European Whites, Han Chinese, Yoruba, and Gujarati Indians, the functional significance of these SNPs requires further investigation.…”
Section: Malaysiamentioning
confidence: 99%
“…Genotyping is a prevailing innovative method used to identify the associations between genetic variations and normal/abnormal phenotypes, especially in clinical and basic research laboratories. Allele frequencies and risk nature of the alleles differ from population to population and genotyping by microarray proves a cost-effective method to determine such differences [5,6]. For many years, multiplex PCR has been the method of choice.…”
Section: Introductionmentioning
confidence: 99%